Oropharyngeal adenocarcinoma as a rare presentaton secondary to gastric adenocarcinoma: a case study - Jain, Rajeev Kumar; Gupta, Deepak Kumar; Bhutia, Chultim Dolma; Chaudhary, Ashvanee Kumar; Singh, Vishwambhar; Mangla, Mohit; Pujari, Lincoln; Dhal, Ipsita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Adenocarcinoma of oropharynx is a rarely encountered entity. It may be primary or secondary as metastasis from a distant site. Secondary adenocarcinoma of base of tongue is even more uncommon, few cases have been reported in the literature till date including one from stomach as a primary site. We are presenting a case of secondary adenocarcinoma of base of tongue metastasised from stomach after one and half years of successful treatment consisting of surgery and adjuvant chemotherapy.